Dampak Program “Bidan Sahabat” Terhadap Peningkatan Penggunaan Layanan Kesehatan Reproduksi Di Komunitas Marginal - Ula, Zumrotul; Atika, Zummatul (Barongko: Jurnal Ilmu Kesehatan, 2025)
Access to and utilization of reproductive health services in marginalized communities remains low due to economic, social, and cultural limitations. The Bidan Sahabat program is a health service innovation that aims to bring midwifery services closer to marginalized communities through a persuasive, community-based approach. This study aims to determine the impact of the Bidan Sahabat program on increasing the utilization of reproductive health services in marginalized communities. This study used a quantitative design with a pretest-posttest quasi-experimental approach without a control group. The sample consisted of 60 women of childbearing age living in marginalized communities and was selected using a purposive sampling technique. Data were collected through a questionnaire on reproductive health service utilization and analyzed using a paired t-test. The results showed a significant increase in the utilization of reproductive health services after the implementation of the Bidan Sahabat program with a p-value <0.05. The conclusion of this study indicates that the Bidan Sahabat program has a positive impact on increasing the utilization of reproductive health services in marginalized communities.